FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION PELANGGAN SUPER INDO DI KOTA BEKASI - Wijaya, Ricky Handika; Indriyanti, Irma Satya (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to empirically test and analyze the effect of Brand Awareness, Perceived Quality, Brand Association, and Brand Loyalty on Super Indo customers' purchase intentions in Bekasi city. The research design used in this research is descriptive research and causality research. This study uses primary data collected by questionnaire.The sampling used was purposive sampling and used 210 respondents. The research data was processed by statistical programs SEM. The results showed that Brand Awareness and Brand Loyalty have a positive and significant effect on Purchase Intention of Super Indo customers in Bekasi City. Brand Awareness and Brand Loyalty can influence Purchase Intention, because it is impossible for a customer to make a Purchase Intention without knowing and being loyal to the brand.